System pomiarowy do diagnozowania dzieci z zaburzeniem koordynacji ruchowej = Measurement system for diagnosis of children with a disorder of motion coordination - Eljasz, Dariusz; Miczulski, Wiesław (1949- ); Powroźnik, Piotr; Sobolewski, Łukasz; Szulim, Robert (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The article presents the structure and principle of operation of a measuring system prototype designed to detect motor coordination disorders (SP_ZKR) in children. A child will be examine while playing mini golf. The obtained results of the SP_ZKR test studies have confirmed the correct operation of the system prototype.
Keywords: systemy pomiarowe; badania przesiewowe; diagnostyka; zaburzenia koordynacji ruchowej